2020
DOI: 10.3233/jad-200214
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the Potential of Robotics for Aged Care Through Co-Creation

Abstract: Socially assistive robots have the potential to improve aged care by providing assistance through social interaction. While some evidence suggests a positive impact of social robots on measures of well-being, the adoption of robotic technology remains slow. One approach to improve technology adoption is involving all stakeholders in the process of technology development using co-creation methods. To capture relevant stake holders' priorities and perceptions on the ethics of robotic companions, we conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…They also enjoyed a companion robot with entertainment functions, including dancing, singing, storytelling, playing board games, or news reporting [ 15 , 25 ]. According to studies, older adults were more receptive to the use of robots for simple and non-intimate physical assistance, such as reminders, domestic chores, and communication, while they were less receptive to the use of robots in activities, such as taking a bath, toileting, and managing finances [ 45 , 48 , 49 ]. Some studies on assisted robots reported that older adults value service-related functions more than companion-related functions [ 20 ], and robot functionality is more important than appearance [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also enjoyed a companion robot with entertainment functions, including dancing, singing, storytelling, playing board games, or news reporting [ 15 , 25 ]. According to studies, older adults were more receptive to the use of robots for simple and non-intimate physical assistance, such as reminders, domestic chores, and communication, while they were less receptive to the use of robots in activities, such as taking a bath, toileting, and managing finances [ 45 , 48 , 49 ]. Some studies on assisted robots reported that older adults value service-related functions more than companion-related functions [ 20 ], and robot functionality is more important than appearance [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported several concerns regarding robots in general. For instance, the complexity of using the robots and technical obstacles impede implementation in the real world [ 49 , 69 ]. Older adults might fear the inability to handle the malfunctioning and rusting of the robot [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If consumer electronics and applications satisfy the minimum competence requirement, then there is already a range of carebots available [69,70]. The simplest current carebots are not too expensive and offer a level of assistance paired with emotive and interactive designs.…”
Section: Virtual Ai Assistive Technologiesmentioning
confidence: 99%
“…In addition, a number of recent studies have shown that older adults were less receptive to intimate robotic physical assistance such as bathing, while they were more open to using robots for simpler tasks such as reminder management and communication. (e.g., Robillard & Kabacińska, 2020). Users also compared robots with pets (Bates, 2019;Lazar et al, 2016), which were more valued thanks to the reciprocity inherent in caring for them and the relationships they form, as well as with other technologies such as those of tablet computers (Mann et al, 2015) and smart home technologies (Torta et al, 2014), which were typically perceived as inferior and less enjoyable than robots.…”
Section: Human-robot Interaction (Hri) In Later Lifementioning
confidence: 99%